Large and Giant Intracranial Aneurysm: Surgical Management and Outcomes in a Tertiary Hospital - Barbarawi MM; Alawneh KZ; Bqour AZ; Qudsieh S; Al Barbarawi AM; Aleshawi A (Vascular Health and Risk Management, 2025)
Mohamed M Barbarawi,1 Khaled Z Alawneh,2 Abedelhalim Z Bqour,3 Suhair Qudsieh,4 Ala’ Moh’d Al Barbarawi,5 Abdelwahab Aleshawi5 1Department of Neurosurgery, Faculty of Medicine, Jordan University of Science & Technology, Irbid, 22110, Jordan; 2Department of Diagnostic Radiology and Nuclear Medicine, Faculty of Medicine, Jordan University of Science & Technology, Irbid, 22110, Jordan; 3Department of Neurosurgery, Ministry of Health, Amman, 11118, Jordan; 4Division of Obstetrics and Gynecology, Department of Clinical Sciences, Faculty of Medicine, Yarmouk University, Irbid, 21163, Jordan; 5Faculty of Medicine, Jordan University of Science & Technology, Irbid, 22110, JordanCorrespondence: Mohamed M Barbarawi, Department of Neurosurgery, Faculty of Medicine, Jordan University of Science & Technology, Irbid, 22110, Jordan, Tel +962 2 7201000, Fax +962 2 7201064, Email mmalbarbarawi@just.edu.joBackground: Large and giant intracranial aneurysms, exceeding 10 mm and 25 mm in diameter, respectively, are rare in neurosurgery. These lesions carry substantial morbidity and mortality risks, often causing mass effects, intracranial hemorrhage, stroke, or seizures.Methods: We present our experience with 54 patients diagnosed with these aneurysms. We conducted neurological assessments and preoperative evaluations using the modified Rankin Scale. Individualized treatment strategies, employing surgical techniques or endovascular embolization, were tailored to each patient.Results: The cohort included 28 females and 26 males, averaging 46.9 years. Aneurysms were predominantly in the anterior circulation (80.6%), with initial symptoms including mass effect (78.7%), cerebral ischemia (8.3%), intracranial hemorrhage (3%), and seizures (2.8%). Surgical interventions, including direct clipping, aneurysmal wall resection, aneurysmorrhaphy with clipping, and cross-clamping (average duration: 20 minutes), were performed in 32 cases (59.2%). Endovascular coiling was utilized in 22 patients (40.8%), with 10 requiring flow diverter stents. Of the cases, 32 were giant aneurysms, and 22 were large aneurysms. Outcomes ranged from favourable to excellent in 70.4% of patients, while 18.5% experienced poor outcomes, primarily in posterior circulation aneurysms or due to poor preoperative conditions. The overall mortality rate was 11.1%, with eight fatalities.Conclusion: Management of giant intracranial aneurysms remains challenging, with higher morbidity and mortality rates compared to other neurosurgical conditions. No universally effective technique exists, emphasizing the importance of meticulous perioperative planning and surgical expertise. Further research and treatment advancements are needed to enhance the management of these complex aneurysms.Keywords: large aneurysm, giant intracranial aneurysm, modified rankin scale, clipping, coiling